Pemberdayaan Ibu-Ibu Melalui Pelatihan dan Pendampingan dalam Mengolah Makanan Berbahan Beras Berbasis Kearifan Lokal untuk Meningkatkan Pendapatan Rumah Tangga - Gultom, Pesta; Nainggolan, Elisabet; Maryati, Desma Erica (Universitas Methodist Indonesia, 2024)
Housewives are often faced with a choice between their roles as mere housewives, or as working mothers who can help add to the household economy. In the current era of digitalization, there are many business opportunities for housewives with small capital that can be opened at any time and can be done independently. Participants in this PKM are housewives in Kampung Johar village, with the aim of developing the creativity of housewives in utilizing agricultural products as village potential. The results of this PKM are in the form of fortified rice milk products. This PKM activity increases the knowledge of housewives and the opportunity to become new entrepreneurs. The methods used in this service are training, mentoring, discussion and question-and-answer methods.